2021
DOI: 10.21608/jppp.2021.178773
|View full text |Cite
|
Sign up to set email alerts
|

Bio-efficiency of some Aromatic Oils and Other Compounds on Some Biological Aspects of Tetranychus urticae as Alternative to Pesticides.

Abstract: Extensive use of conventional pesticides and acaricides to control of the two spotted spider mite, Tetranychus urticae Koch caused undesirable side effects on environment, humans and animals so, it was necessary to look for alternative control methods including the use of aromatic oils and natural oils, as botanical acaricides . The present study was carried out to assessment bio-efficiency of some aromatic oils and other compounds on some biological aspects of T. urticae in laboratory at (25±2) ºC, and (65±5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…These outcomes are in agreement with those of Elsadany et al (2021) that hypothesized that one of the main signs in the development of a resistant strain is the reduction in the slope of the dosage mortality line, in this way one can expect that compounds with low slope value might prompt to improve resistance if utilized successively. Assessing the toxicity of a pesticide to phytoseiids by estimating female mortality alone underestimates the true effect of residual exposure (Irigaray et al, 2007).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These outcomes are in agreement with those of Elsadany et al (2021) that hypothesized that one of the main signs in the development of a resistant strain is the reduction in the slope of the dosage mortality line, in this way one can expect that compounds with low slope value might prompt to improve resistance if utilized successively. Assessing the toxicity of a pesticide to phytoseiids by estimating female mortality alone underestimates the true effect of residual exposure (Irigaray et al, 2007).…”
Section: Resultssupporting
confidence: 91%
“…In addition, results showed that Romectin gold displayed higher slope (0.683) over AgriFlix (0.439). Elsadany et al (2021) reported that the slope value is considered as an indicator of the reaction between the chemical and the tested organism. As the highest slope value means greater homogeneity of the organism response towards the pesticide, whereas the low slope value demonstrates heterogeneous response of the organism to the tested chemical.…”
Section: Resultsmentioning
confidence: 99%